Sedation rates of patients with autism spectrum disorder in the emergency department: a case-matched cohort study - Arasu, Ramesh; Das, Soumitra; Thomas, Naveen (Frontiers in Psychiatry, 2025)
IntroductionAdult patients with autism spectrum disorder (ASD) exhibit a range of behaviours that can be disruptive to the medical care of themselves and other patients and as a result, may be at higher risk of requiring chemical sedation. These autistic individuals often experience communication difficulties, sensory sensitivities, and high rates of psychiatric comorbidities, which can exacerbate distress and behavioural dysregulation during acute episodes. This complexity may contribute to an increased reliance on chemical sedation during emergency care. The aim of the present study was to determine whether patients with ASD presenting to hospital for acute psychiatric crises receive more sedative medications compared to similar patients without ASD.MethodsIt is a retrospective case matched control study. 66 presentations from adult patients with a previous diagnosis of ASD who were referred to the mental health team at a single, large emergency department in metropolitan Victoria over the year of 2021 were identified and matched with controls from the same cohort at a 2:1 ratio. The matching was done between age and sex. The number of times each patient was sedated was compared using univariate and multivariate logistic regression, adjusting for other recorded characteristics.ResultsPatients with ASD had 4.83 times the odds of receiving multiple doses of sedatives compared to matched controls when controlling for all non-matched characteristics (95%CI: 1.96-11.94, χ²=64.47, df=10, p<0.001). There was no significant difference in the rates of intramuscular sedation nor mechanical or physical restraint.DiscussionClinicians should be aware of the increased rate of receiving multiple doses of sedatives and consider other means of behavioural management in patients with ASD